Take the 2-minute tour ×
Physics Stack Exchange is a question and answer site for active researchers, academics and students of physics. It's 100% free, no registration required.

I'm given this commutator: $$\left[PXP,P\right]$$ Being $P\psi=-i\hbar\partial_x\psi$, and $X\psi=x\psi$

I've solved it in two ways, the first one is just aplying the commutator to some function $\psi$ and see what I get. My final result is: $$\left[PXP,P\right]=-i\hbar^3\partial_{xx}$$ The second one is using some commutator properties: $$\left[PXP,P\right]=-\left[P,PXP\right]=-(P\left[P,XP\right]+\left[P,P\right]XP)$$ $\left[P,P\right]=0$, so the second term goes away. I again expand the first term: $$-P\left[P,XP\right]=-P(X[P,P]+[P,X]P)=-P[P,X]P=i\hbar P^2=\boxed{-i\hbar^3\partial_{xx}}$$

I again get the same result. When the teacher solved it in class, the final result was: $$\left[PXP,P\right]=2i\hbar P^2$$ I have no idea where that $2$ comes from. Am I missing something? Am I doing something wrong?

share|improve this question
add comment

2 Answers 2

up vote 2 down vote accepted

You teacher seems to have made a mistake. I imagine that he/she did something like this: \begin{align} [PXP, P] &= P[XP,P]+[PX,P]P \\ &= P(X[P,P]+[X,P]P)+(P[X,P]+[P,P]X)P \\ &= P[X,P]P+P[X,P]P \\ &= 2i\hbar P^2 \end{align} Notice that the first equality is wrong. You can't peel operators off to the left and right if there are three operators in the first slot of the commutator!

share|improve this answer
    
+1 @MyUserIsThis 's conclusion was obviously correct, but I couldn't see what kind of mistake could have given a $2$. As an extra check for the OP, using $[AB,C] = A[B,C] + [A,C]B$ is apparently identity the teacher tried to use, which applied twice would give $[PXP,P] = P[XP,P] + [P,P]XP = PX[P,P] + P[X,P]P = i\hbar P^2$. –  Stan Liou Apr 26 '13 at 22:25
    
ok, thanks you very much –  MyUserIsThis Apr 26 '13 at 23:35
add comment

I think you are right. Using really simple commutator math. All you need is this: $$ [AB,C] = A[B,C] + [A,C]B $$ Then in your case: $$ A=P$$ $$B=XP$$ $$C=P$$ $$ [PXP,P] = PX [P,P] + [P,P]XP = PX[P,P] + P[X,P]P + [P,P] XP $$ As you said, [P,P] is antisymmetric to itself, and therefore we can remove all the [p,p] terms. We then have left only one term: $$[PXP,P] = P[X,P]P$$ and as you know (we defined the operators so they do this) $$[X,P]= i \hbar$$

So we can write: $$P(i \hbar) P$$. We can move out the scalar so: $$[PXP,P] = i \hbar P^2$$

I can't find anything wrong with any of my steps, so I am pretty sure the 2 should not be there

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.